Modification of the National Inpatient Medication Chart improves venous thromboembolism prophylaxis rates in high‐risk medical patients. Issue 2 (February 2014) - Yates, M.; Reddy, M.; Machumpurath, B.; Phelps, G.; Hampson, S.‐A.
Abstract Background Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality in Australia. While there is well‐established evidence for the use of VTE prophylaxis in hospital inpatients, adherence to such guidelines is poor. Aim The aim of the present study is to assess the impact of education and system change on improving rates of VTE prophylaxis in hospital inpatients. Methods We performed four consecutive audits of inpatient medical records of a regional hospital service over 2 years. The audits aimed to test the impact of serial interventions at increasing the appropriate use of VTE prophylaxis (based on risk assessment). The interventions were (i) staff education and (ii) a process change that mandated a prophylaxis decision by modifying the National Inpatient Medication Chart with 'VTE avoidance' preprinted in the first medication box. Results Our results from the baseline study showed that of the 236 medical inpatients reviewed, 80% were at high risk of VTE. Of this high‐risk cohort, 34.9% (confidence interval (CI) 28–42%) had appropriate prophylaxis decisions. Post the education intervention, 43.2% (CI 37–49%) of the high‐risk cohort received appropriate VTE prophylaxis, an improvement of 8.3% (CI −1% to 18%) from baseline. With the subsequent introduction of a process change, 82.1% (CI 66–92%) of the high‐risk cohort received appropriate prophylaxis, an improvement of 47.2% and 38.8% (CI 24–54%) when compared with baseline and education respectively. Retention rates at 11 months postsystem change were 73% (CI 55–86%). Conclusions This study therefore concluded that while education has an impact on rates of appropriate VTE prophylaxis, it is system change that has the most marked and sustained effect.